Strategic Management of Human Resources in the Health Care System - Kanellopoulos, Dimitrios (Richtmann Publishing, 2012)
Development of the strategy in the health care system cannot be done without granting special attention over humanresources. These are an important component in any system and influences the evolution and actual situations by theirsubjective dimensioning. HR management should actively participate in drafting the strategy, having in consideration therelatively long time stamp of the strategy. This participation is determined by the time needed to ensure appropriate andadjustable human resources to the strategy considered. The activities specific to the planning, organization, coordination,training and evaluating human resources are expensive activities which impose a special attention, particularly because it affectsdirectly the achievement of the proposed objectives.